2008 financial crisis versus 2020 economic fallout: how COVID-19 might influence fertility treatment and live births. Issue 6 (June 2021) - Gromski, Piotr S.; Smith, Andrew D.A.C.; Lawlor, Deborah A.; Sharara, Fady I.; Nelson, Scott M.
Abstract: Research question: The economic and reproductive medicine response to the coronavirus disease 2019 (COVID-19) pandemic in the USA has reduced the affordability and accessibility of fertility care. What is the impact of the 2008 financial recession and the COVID-19 recession on fertility treatments and cumulative live births? Design: The study examined annual US natality, Centers for Disease Control and Prevention IVF cycle activity and live birth data from 1999 to 2018 encompassing 3, 286, 349 treatment cycles, to estimate the age-stratified reduction in IVF cycles undertaken after the 2008 financial recession, with forward quantitative modelling of IVF cycle activity and cumulative live births for 2020 to 2023. Results: The financial recession of 2008 caused a 4-year plateau in fertility treatments with a predicted 53, 026 (95% confidence interval [CI] 49, 581 to 56, 471) fewer IVF cycles and 16, 872 (95% CI 16, 713 to 17, 031) fewer live births. A similar scale of economic recession would cause 67, 386 (95% CI 61, 686 to 73, 086) fewer IVF cycles between 2020 and 2023, with women younger than 35 years overall undertaking 22, 504 (95% CI 14, 320 to 30, 690) fewer cycles, compared with 4445 (95% CI 3144 to 5749) fewer cycles in women over the age of 40 years. This equates to overall 25, 143 (95% CI 22, 408 to 27, 877) fewer predicted live births from IVF, of which only 490 (95% CI 381 to 601) are anticipated to occur in women over the age of 40 years. Conclusions: The COVID-19 recession could have a profound impact on US IVF live birth rates in young women, further aggravating pre-existing declines in total fertility rates.